Malta : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 1999)
This Selected Issues paper and Statistical Appendix analyzes the fiscal and structural issues affecting Malta's economic performance, specifically the public enterprises and the tax system. The paper focuses on exchange rate policy and macroeconomic and legislative issues in the context of European Union membership. The standard summaries of the tax system and recent developments in the exchange and trade system are presented. The paper highlights that despite advances in the financial sector deregulation, tax reform, and trade liberalization during the 1990s, there are still key structural inadequacies in Malta.